ANALISIS IMPLEMENTASI KOMPENSASI KARYAWAN PT. LOTTE SHOPPING INDONESIA CABANG PEKANBARU - Teti Ernawati; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Compensation is one of the important functions of Human Resource Management. Because compensation is the most sensitive aspects of the employment relationship. Cases occurring in the employment relationship and the compensation issue contains a variety of related terms, such as benefits, compensation increases, compensation structure, and the scale of compensation. Compensation system is helpful in strengthening the key values of the organization and facilitate the achievement of organizational goals.This research was conducted at PT. Lotte Shopping Indonesia Pekanbaru Branch. Located on Jl. Soekarno Hatta 50. The purpose of this research was conducted to analyze the implementation of compensation kryawan PT. Lotte Shopping Indonesia Pekanbaru Branch. In this research methodology used is descriptive analysis where the sample used is an employee of PT. Lotte Shopping Indonesia Pekanbaru Branch. The technique of collecting data through questionnaires and interviews.Implementation and Analysis of the results of Employee Compensation in PT. Lotte Shopping Indonesia Pekanbaru Branch which includes salary, benefits and incentives, stating that compensation has been applied are in either category.Keyword: salaries, benefits, incentive.